Multi-depth evolution characteristics of soil moisture over the Tibetan Plateau in the past 70 years using reanalysis products - Liu, Yangxiaoyue; Yang, Yaping (Frontiers in Environmental Science, 2022)
Soil moisture is a crucial component of the hydrological cycle. Both the spatial-temporal distribution and variation characteristics of SM are effective indicators of regional land surface water resource homogeneity and heterogeneity. Considering the crucial role of the Tibetan Plateau (TP) in the hydrological process in Asia, this study investigates the fluctuation of multi-depth soil moisture over the TP during 1950–2020 on a monthly scale under the background of global warming using ERA5 reanalysis datasets. The correlation and potential causality between soil moisture and associated driving factors were explored. Our research revealed that the soil moisture over the TP shows a slight wetting trend at 0–100 cm depth for the past 70 years under the background of climate warming and increasing precipitation. Additionally, the wetting region (variation trend ≥ 0.005 m3/m3 per decade) had sufficient water supplementation from precipitation and a mild soil temperature increase. In comparison, there is a noteworthy warming tendency and falling precipitation in the sparsely distributed drying region (variation trend ≤ -0.005 m3/m3 per decade). In terms of vertical variation features, the temporal dynamic fluctuation of soil moisture and soil temperature evidently decreases as depth increases, suggesting the high sensitivity of the surface layer soil to atmospheric conditions. Precipitation and snowmelt preliminarily proved to be the dominant drivers causing the spatial and temporal variation of soil moisture (occupying over 70% of the TP region), and bidirectional causality (ranging between 15.52–50.56%) was found between soil moisture and these two parameters. The evaporation then changes, induced by the joint efforts of raising temperature and SM supplementation. In summary, this study explores the spatial-temporal fluctuation in the evolutionary characteristics of SM, which is expected to advance our understanding of soil moisture dynamics under the condition of climate change over the TP.